Low adherence to dietary recommendations in adult childhood cancer survivors. Issue 5 (October 2017) - Belle, Fabiën; Wengenroth, Laura; Weiss, Annette; Sommer, Grit; Beck Popovic, Maja; Ansari, Marc; Bochud, Murielle; Kuehni, Claudia; ,
Summary: Background & aims: Poor diet may increase the risk that childhood cancer survivors (CCS) will suffer from chronic disease. We compared adherence to national dietary recommendations between CCS, their siblings and the Swiss population, identified determinants of adherence, and assessed the association of adherence with cardiovascular disease (CVD) risk profiles. Methods: As part of the Swiss Childhood Cancer Survivor Study (SCCSS), a questionnaire was sent to all Swiss resident CCS aged <21 years at diagnosis, who survived ≥5 years and were 16–45 years old at the time of the survey. We compared dietary adherence between CCS, their siblings and participants in the Swiss Health Survey (SHS), a representative survey of the general population. A multivariable logistic regression was used to assess characteristics associated with dietary adherence. We sorted CCS into four kinds of CVD risk groups based on type of treatment (anthracyclines, chest irradiation, a combination, or neither). Results: We included 1864 CCS, 698 siblings and 8258 participants of the general population. Only 43% of the CCS met the recommended dietary intakes for meat, 34% for fruit, 30% for fish, 18% for dairy products, 11% for vegetables, and 7% for combined fruit and vegetables. Results were similar for both control groups. In all groups, dietary adherence was associated with gender, parental education, migration background, language region in Switzerland, smoking, alcohol consumption and sport participation. CCS with a higher CVD risk profile because of cardiotoxic treatment had no better adherence. Conclusions: CCS have similar food patterns as their siblings and the general population, and poorly adhere to current recommendations. Awareness of the importance of a healthy diet should be raised among CCS, to prevent chronic diseases like CVD.